2020
DOI: 10.1027/2192-0923/a000192
|View full text |Cite
|
Sign up to set email alerts
|

Review of Aviation Safety Databases to Identify Information Discrepancies Experienced on the Flight Deck

Abstract: Abstract. Aeronautical decision-making on the flight deck requires pilots to reconcile and make decisions using information from a range of different sources, sometimes with limited knowledge of associated levels of accuracy, integrity, and reliability. A review of four aviation safety databases identified information discrepancies experienced by general aviation and airline pilots. The analysis captured current trends in (a) the information discrepancies that pilots experience on the flight deck, (b) how pilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Carstens et al [16] examined four aviation safety databases in order to identify the trends in information discrepancies and how pilots are responding to them. They searched through the Aviation Safety Reporting System (ASRS) database, the National Transportation Safety Board (NTSB) accident database, the FAA Accident and Incident Data System (AIDS) database and the Aviation Safety Action Program (ASAP) database from a major United States-based airline.…”
Section: Empirical Supportmentioning
confidence: 99%
“…Carstens et al [16] examined four aviation safety databases in order to identify the trends in information discrepancies and how pilots are responding to them. They searched through the Aviation Safety Reporting System (ASRS) database, the National Transportation Safety Board (NTSB) accident database, the FAA Accident and Incident Data System (AIDS) database and the Aviation Safety Action Program (ASAP) database from a major United States-based airline.…”
Section: Empirical Supportmentioning
confidence: 99%
“…Mosier et al (2007) conducted a study in which pilots were faced with information conflicts between an automated source and other sources, such as an airspeed indicator, and found that information conflicts led to significantly less accurate problem diagnoses and longer response times. Carstens et al (2020) conducted a review of aviation safety data bases from 2007 to 2017 and found that of the 56 incidents and accidents involving information discrepancies on the flight deck, 36 (64%) resulted in a significant performance or safety impact such as an a near miss or runway incursion.…”
mentioning
confidence: 99%